A time-dependent offset field approach to simulating realistic interactions between beating hearts and surgical devices in virtual interventional radiology - Wang, Haoyu; Wu, Jianhuang (Frontiers in Cardiovascular Medicine, 2022)
Endovascular interventional radiology (IR) is a minimally invasive procedure for the treatment of vascular diseases. This procedure requires physicians to be highly skilled at manipulating interventional devices under the guidance of two-dimensional X-ray imaging. By offering a non-error-sensitive and radiation-free environment, a virtual reality-based simulator provides a promising alternative for surgical skills training and surgery planning. Building a realistic and interactive simulator is a challenging task. To achieve better realism, this paper proposes a novel method of simulating the heartbeat for both standard and patient-specific anatomical data. A time-dependent offset field approach is proposed to efficiently and stably simulate the interactive behavior between the dynamic heart mesh and surgical devices. For medical imaging simulation, we propose a GPU-based linear depth subtraction method to approximate fluoroscopic images based on the attenuation of the X-ray. On this basis, a topology-based flow map method is proposed to simulate the propagation of the contrast medium in angiography. Experimental results show that the proposed algorithm can simulate heartbeat stably for meshes with varying geometrical shapes and complexities. In efficiency, the dynamic heart mesh can interact with surgical devices stably at 60 frames/s. Under the simulated fluoroscopic imaging effect, the injected contrast medium can realistically visualize both dynamic and static vessels. In a face validity by medical students and clinicians, the category of effectiveness score 8.35 out of 10 on average, demonstrating that our simulator is useful in surgical skills training and surgery planning.